Proprotein Convertase Subtilisin/Kexin 9 Levels in Relation to Systemic Immune Activation and Subclinical Coronary Plaque in HIV. (14th October 2017) - Zanni, Markella V; Stone, Lauren A; Toribio, Mabel; Rimmelin, Dodie E; Robinson, Jake; Burdo, Tricia H; Williams, Kenneth; Fitch, Kathleen V; Lo, Janet; Grinspoon, Steven K
Abstract: Background: Proprotein convertase subtilisin/kexin 9 (PCSK9) is known to mediate homeostasis of low-density lipoprotein cholesterol (LDL-c), but it may also participate in immune reactivity and atherogenesis. Methods: We compared circulating PCSK9 levels among asymptomatic individuals with and without HIV. Further, within each group, we assessed the relationship between PCSK9 levels, traditional cardiovascular disease risk factors, immune activation, and subclinical coronary atherosclerotic plaque. Results: PCSK9 levels were higher among HIV-infected (n = 149) vs matched non-HIV-infected subjects (n = 69; 332 [272, 412] ng/mL vs 304 [257, 375] ng/mL; P = .047). Among HIV-infected subjects, significant albeit modest positive associations were noted between PCSK9 levels and markers of systemic monocyte activation including sCD14 ( rho = 0.22; P = .009) and sCD163 ( rho = 0.23; P = .006). In this group, PCSK9 levels related weakly to LDL-c ( rho = 0.16; P = .05) and also to Framingham Point Score but did not relate to subclinical coronary atherosclerotic plaque parameters. Conclusions: Among HIV-infected individuals, circulating PCSK9 levels are elevated and related to systemic markers of monocyte activation but not to coronary plaque parameters. Additional studies are needed to determine the effects of PCSK9 on immune activation and atherogenesis in HIV and to assess whether PCSK9 inhibition reduces immune activation and coronary atherosclerotic plaque burden. Clinical Trial Registration: NCT00455793.